A political ecology of green territorialization: frontier expansion and conservation in the Colombian Amazon - Hein, Jonas; Del Cairo, Carlos; Gallego, Daniel Ortiz; Gutiérrez, Tomás Vergara; Velez, Juan Sebastian; Rodríguez de Francisco, Jean Carlo (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
After decades of civil war, the Colombian government has recently declared the Amazon as a model region for green growth and low carbon development. The Amazon Vision programme, launched by the Colombian government in 2016, seeks to contribute to forest conservation, climate mitigation, poverty reduction and peace building. The Amazon Vision fundamentally reframes the Colombian Amazon from a ‘narco frontier’ that needs to be liberated from guerrilla influence, organized crime and peasants destroying forests for coca cultivation, to a net CO2 sink with enormous potential for green growth and poverty reduction. Drawing on historical and empirical qualitative research in Guaviare and complemented by a quantitative land cover classification, this article builds on the concept of ‘green territoriality’ to investigate the extent to which the shift towards conservation affects property rights and the ability of indigenous groups and peasants to access land and natural resources. We illustrate how the reframing of peasants from protagonists of development and frontier expansion to villains, and of indigenous communities from underdeveloped forest dwellers to environmental guardians, has created land conflicts and affected the legitimacy of their respective property rights. In both cases, the Amazon Vision strengthens conservation policies and challenges existing land rights but also creates new windows of opportunity for the land claims of indigenous communities while reinforcing conceptualizations of social differentiation among dwellers of the Amazon.